Promoting sustainable development in less-favored areas - Pender, John L.; Hazell, Peter B. R. (International Food Policy Research Institute, 2000)
Poverty, low agricultural productivity, and natural resource degradation are severe interrelated problems in less-favored areas of the tropics. Less-favored areas include lands that have low agricultural potential because of limited and uncertain rainfall, poor soils, steep slopes, or other biophysical constraints, as well as areas that may have high agricultural potential but have limited access to infrastructure and markets, low population density, or other socioeconomic constraints (see figure). In other words, less-favored lands may be less favored either by nature or by man.